The examination of human resources in the Hódmezővásárhely micro-region on the basis of human resource hierarchy - Kis, Krisztián (Acta Agraria Debreceniensis, 2008)
In this paper, I deal with the examination of the situation and change of human resources through the human resource hierarchy. My research covers the Hódmezővásárhely micro-region, which includes four settlements, two towns (Hódmezővásárhely as the centre of the area and Mindszent) and two villages (Mártély and Székkutas). Based on population density the micro-region is qualified as a rural territory, which is underpinned by the micro-region’s market town and homestead like character.I took the human resource system of Cloke and Park (1985) published in their book of Rural Resource Management as a basis of my examination and I pursued my research in consideration of Fehér’s (2005) researches related to rural economy. The system of human resources provided a hierarchical and logical framework for my examination. In the course of the research I made analyses along the three levels of human resources concerning the micro-region and its settlements.During the examination of the human resources of the Hódmezővásárhely micro-region I pointed out some negative changes and situations which unfavourably influence the socio-economic processes of the territory and its settlements. All this reveal that the human resources are not only factors of the economy of the micro-region as a rural economy but at the same time they are areas to be developed. The living standard (welfare) of the people living in the area and their quality of life (well-being) depend on the development and level of the different dimensions of the human resources largely. For that very reason there is a need for coordinated development of the human resources and the related fields with respect to the cause-effect relations.My research contributes to the better cognition of rural resources of the Hódmezővásárhely micro-region, without this a rational improvement and sustainable development of the micro-region and its settlements based on inner resources cannot be imagined.